A responsabilidade da federação russa pelo uso de armas incendiárias no conflito Armado Sírio - Moreno, Neylson de Jesus Gonçalves (Universidade Federal Rural do Semi-Árido, 2017)
This article focuses on the analysis of the military action of the Russian Federation in the Syrian armed conflict regarding the air attacks on the civilian areas of the cities of Aleppo and Idlib, an episode reported by the Human Rights Watch, an Human Right organization, to the International Community. The legal consequences according to International Humanitarian Law of the use of incendiary weapons reported in the attacks are being questioned. The legal analysis of the use of such weapons is important because of the destruction effects caused by the attacks on life and human health that they have legal protection under International Humanitarian Law. This analysis is based on the deductive method of the provisions of Geneva Conventions and Additional Protocols, Hague Conventions and The Protocol on Prohibitions or Restrictions on the use of Incendiary Weapons (Protocol III) of Convention on Certain Conventional Weapons, and supported by documental and bibliographical sources. This research is divided into three parts. The first part explains the treatment that applies to the use of incendiary weapons by International Humanitarian Law. Then, principles of International Humanitarian Law are described to demonstrate that it is possible for a settlement of dispute between the International Community and the Russian Federation to be considered to the judgment of the International Court of Justice. In The last part, it analyzes the liability of the Russian Federation for the use of incendiary weapons in the Syrian armed conflict. The research shows that there has been a breach by the Russian Federation the obligation of “to respect and to ensure” International Humanitarian Law. This noncompliance allows the international community to seek liability of the Russian Federation to the International Court of Justice for the damage caused to States Parties to the Geneva Conventions, as they are being morally violated by direct attacks on Syrian cities.
Artigo Acadêmico
Keywords: Direito Internacional Humanitário; Armas incendiárias; Conflito Armado Sírio; Corte Internacional de Justiça; Responsabilidade Internacional do Estado; International Humanitarian Law; Incendiary weapons; Syrian Armed Conflict; International Court of Justice; International State Liability; CIENCIAS SOCIAIS APLICADAS::DIREITO